Protecting Children and Supporting Families post-Covid - Brid Featherstone (Social Work and Society)
In this article, the author revisits her work on the Social Model of Protecting Children. This work is based on research into social inequalities and social harms and poses a challenge to the individualising child protection narratives that have dominated in England, the country the article is based on. The author explores the possibilities thrown up by Covid 19, for supporting shifts towards a social model. It will be argued, however, that while there were, indeed, such possibilities, subsequent explorations have raised troubling questions particularly concerning the role of the contemporary state in England. The article concludes by highlighting some conceptual and empirical resources to support renewed critique and activism going forward.